Baccharis dracunculifolia DC. (Asteraceae): composição do óleo essencial, diversidade e parâmetros genéticos - Belini, Camila Moreira Batista [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Baccharis dracunculifolia species can be used in the recovery of deforested areas and disturbed by agricultural activities in addition to providing many health benefits, but there are no germplasm collections of seeds and seedlings to meet this demand, which may result in inadequate exploitation of the species as it happened to Baccharis trimera. In this context, the purpose of this work is to provide subsidies for the sustainable exploitation of the species, as well as the development of genetic improvement for essential oil production and the formation of a germplasm bank of seeds with wide genetic variability. The plant materials used for this study were divided into two groups, were collected in an altitudinal gradient, plant natural populations in Campos do Jordão, Ubatuba, and Campinas. 56 constituents were found in the essential oil composition, extracted by hydrodistillation, natural populations studied in the years 2012 and 2013, with only eight constituents common to all populations, the trans-nerolidol compound was the major substance for all populations (ranging from 21.6 to 40.8%), These populations are well structured chemically suggesting that there is the influence of altitude, especially for the chemical compounds of the population of Campos do Jordão. In the other group, it was a test provenances and progenies installed in CPQBA/UNICAMP, in which it evaluated the essential oil yield extracted by distillation by steam distillation of water and fresh mass of shoots for the estimation of genetic parameters, the yield ranged from 0.1% to 0.3%, and no significant differences were observed between the averages. The yield of essential oil kg/1000 m2 on average, ranged from 13 to the population of Campinas 15 for the population of Ubatuba. The characteristic of weight, on average, the progeny was higher for the population of Campinas (1.6 kg), followed by Ubatuba ...

A espécie Baccharis dracunculifolia pode ser utilizada na recuperação de áreas degradadas e antropizadas por atividades agrícolas além de proporcionar diversos benefícios à saúde, todavia não existem bancos de germoplasma de sementes e mudas para atender a esta demanda, o que poderá acarretar na exploração inadequada da espécie como aconteceu à Baccharis trimera. Dentro desse contexto, a finalidade deste trabalho é a de fornecer subsídios para a exploração sustentada da espécie, bem como, o desenvolvimento do melhoramento genético para produção de óleo essencial e para a formação de um banco de germoplasma de sementes com ampla variabilidade genética. Os materiais vegetais utilizados para este estudo foram divididos em dois grupos, foram coletadas, num gradiente altitudinal, plantas de populações naturais em Campos do Jordão, Ubatuba, e Campinas. Encontrou-se 56 constituintes na composição do óleo essencial, extraído por hidrodestilação, das populações naturais estudadas nos anos de 2012 e 2013, sendo, somente, oito constituintes comuns a todas as populações, o composto transnerolidol foi a substância majoritária para todas as populações (variando de 21,6 a 40,8%), Essas populações estão bem estruturadas quimicamente sugerindo que há a influência da altitude, em especial para os compostos químicos das populações de Campos do Jordão. No outro grupo, foi um teste de procedências e progênies instalado no CPQBA/UNICAMP, no qual se avaliou a produtividade de óleo essencial extraído por destilação por arraste a vapor d'água e massa fresca de da parte aérea para as estimativas de parâmetros genéticos, o rendimento variou de 0,1% a 0,3% e, não foram observadas diferenças significativas entre as médias. A produtividade do óleo essencial em ...
Baccharis dracunculifolia DC. (Asteraceae)
Keywords: Plantas medicinais; Óleos vegetais - Composição; Diversidade genética; Medicinal plants